METODE CERTAINTY FACTOR UNTUK MENDETEKSI PENYAKIT CABAI KERITING - Ahmad Fahrurohim; Sri Siswanti; Bebas Widada (STMIK Sinar Nusantara, 2020)
The disease of kinky chili plants that often experience diseases such as brown spots on the leaves, wither Fusarium, Wilt bacteria, rotten leaves. This disease often affects these kinky chili plants can harm farmers like failing plants and can cause plants to die. The purpose of this research is to design an application used to diagnose diseases in curly chili peppers, so that by the method of certainty factors can know the type of plant diseases in curly chili peppers. The method used is a method of certainty factor because this method is used to overcome uncertainty in decision making by measuring the facts or rules. Data collection methods that include interviews with an expert, so the data can be trusted by the truth. To reinforce the research analysis is also looking for information by reading book journals, books and literature in the library and online. Steps to make an implementation of the method of certainty factor in detecting curly chili disease, it is designed to design concepts, collect data, prepare hardware and software, create an application creation diagram Modeling, testing, repair, and resolution. Based on the testing of BlackBox on the system, this system is declared functioning according to user commands. And the targeted testing of the validity of manual calculations and system calculations, declared valid with a 93.77% trust percentage value.